Human rights after Hitler : the lost history of prosecuting Axis war crimes - Plesch, Daniel (2017)
Human Rights after Hitler is a groundbreaking history about the forgotten work of the UN War Crimes Commission (UNWCC), which operated during and after World War II in response to Axis atrocities. He explains the commission's work, why its files were kept secret, and demonstrates how the lost precedents of the commission's indictments should introduce important new paradigms for prosecuting war crimes today. The UNWCC examined roughly 36,000 cases in Europe and Asia. Thousands of trials were carried out at the country-level, and hundreds of war criminals were convicted. This rewrites the history of human rights in the wake of World War II, which is too focused on the few trials at Nuremberg and Tokyo. Until a protracted lobbying effort by Plesch and colleagues, the UNWCC's files had been kept out of public view in the UN archives under pressure from the US government. The US initially wanted the files closed to smooth the way for post-war collaboration with Germany and Japan, and the few researchers who did gain permission to see the files were not permitted to even take notes until the files' recent release. Now revealed, the precedents set by these cases should have enormous practical utility for prosecuting war crimes today.
Prosecuting rape : the modern relevance of WW2 legal practice -- Key issues faced in prosecuting SGBV today -- Conclusion -- A new paradigm for providing justice for international human rights violations -- Legal and political amnesia -- Creation of the UNWCC -- Official resistance to prosecuting war crimes -- Chinese and Indian leadership -- A global system of complementary justice -- The development of key international legal principles -- Conclusion -- When the Allies condemned the Holocaust -- Early Allied condemnations of the Holocaust and Nazi atrocities -- The declaration -- Abandonment of the Jews nonetheless -- Conclusion -- Pursuing war criminals all over the world -- A global achievement -- Commission members and court structures -- Conclusion -- The Holocaust indictments : prosecuting the "footsoldiers of atrocity" -- Belgium -- Czechoslovakia -- Denmark -- France -- Greece -- Luxembourg -- The Netherlands -- Norway -- Poland -- Yugoslavia -- United Kingdom -- United States -- Conlusion -- Fair trials and collective responsibility for criminal acts -- The fundamentals of fair trials -- "It wasn't illegal when the action was taken" -- Hearsay -- The rights of the accused -- Command responsibility -- Superior orders -- Group responsibility -- Conspiracy and common design -- Reprisals and the execution of hostages -- Securing the rights of the accused -- Conclusion -- Crimes against humanity : the "freedom to lynch," and the indictments of Adolf Hitler -- Crimes against humanity -- The crimes of aggression and genocide -- Universal jurisdiction -- Conclusion -- Liberating the Nazis -- Forgetting the Nazi past to build a West German future -- Early protests against prisoner release -- Hostility to the commission -- Opposition to the commission's closure -- Ongoing prosecution of war crimes -- Prisoner release -- Conclusion -- The legacy unleashed -- The peoples' human rights -- The UNWCC as an international human rights agreement -- Complementarity and the UNWCC -- Toward a "UNWCC 2.0"? -- Conclusion -- Appendix A : Timeline of the Allies' principal political responses to Axis atrocities -- Appendix B : A note on the UNWCC archives and related material -- Appendix C : The role of the UNWCC in obtaining ICTY verdicts -- Appendix D : An early UNWCC charge file against a group of Germans involved in the Treblinka Death Camp -- Appendix E : An early Polish charge file against a group of Germans involved in the concentration camp system.
Includes bibliographical references and index.
Keywords: United Nations War Crimes Commission -- History; United Nations War Crimes Commission; United Nations War Crimes Commission; Vereinte Nationen -- War Crimes Commission; 1900-1999; War crime trials -- History -- 20th century; World War, 1939-1945 -- Atrocities; Holocaust, Jewish (1939-1945) -- Historiography; Atrocities; Historiography; War crime trials; Judenvernichtung; Kriegsverbrechen; Strafverfolgung; Weltkrieg; 2; History